1,4-Dithiaheterocycle-fused porphyrazines: Synthesis, characterization, voltammetric and spectroelectrochemical properties - KOCA, ATIF (ELSEVIER SCI LTD, 2009)
Porphyrazines (M = H, Mg, Zn and Co) with a 2,3-dicyano-5-phenyl-5,6-dihydro-1,4-dithiin group fused to each pyrrole unit were synthesized and characterized starting with the corresponding unsaturated dicarbonitrile derivative. The voltammetric and spectroelectrochemical characterizations of the metallo-porphyrazines (M=2H(+), Mg2+, Zn2+ and Co2+) substituted with 2,3-dicyano-5-phenyl-5,6-dihydro-1,4-dithiin groups on peripheral positions are described. Cyclic voltammetry and differential pulse voltammetry studies showed that while metal-free, magnesium, and zinc porphyrazines represented well-defined one-electron ligand-based reductions and ligand-based one-electron oxidation couples, cobalt porphyrazine gave both metal-based and ligand-based reduction and oxidation couples. Assignments of the redox couples were confirmed by spectroelectrochemical measurements. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Porphyrazines; Phthalocyanines; Magnesium; Cobalt; Zinc; Electrochemistry; Cyclic voltammetry; Spectroelectrochemistry; ZINC PHTHALOCYANINE COMPLEXES; DISODIUM DIMERCAPTOMALEONITRILE; METAL-FREE; BEHAVIOR; METALLOPHTHALOCYANINES; THIACYANOCARBONS; SUBSTITUENTS; OXIDATION; MANGANESE; COBALT